Studi elemen interface model hiperbolik dan hiss untuk analisis dan desain dalam geoteknik - Perpustakaan UGM, i-lib ([Yogyakarta] : Fakultas Psikologi Universitas Gadjah Mada, 1998)
ABSTRACT Many geotechnical engineering problems involved a soil-structure interaction. These problems are very complex, because a soil-structure interaction is a complex behavior of soils. Most of those problems are solved by neglecting the influence of soil-structure interface. This research studies the behavior of soil-pile interface and the effect of interface element in numerical analysis with non linear finite element program. For the purpose of modeling the soil and interface more realistically in non linear finite element simulations need both the soil and interface parameters. A Hyperbolic soil model, a hyperbolic interface model and a HiSS interface model are used in this research. The soil parameters are based on conventional triaxial compression test result and the interface parameters are taken from the modified direct shear test result. The interface element modeling used zero thickness interface element from Plesha at all. (1989). Small scale model pile test was performed with load and displacement measurements. This model test is also simulated in non linear finite element program that is supported by hyperbolic and HiSS soil and interface models. So, it can verify and study the interface behavior, interface element role and the reliable of the non linear finite element program. Case study in the field is also done to evaluate the instrument load test. Typical comparisons between finite element simulations and field data show that the HiSS interface model gave a better performance rather than the hyperbolic interface model. Hyperbolic soil and interface models aplication on instrumented load test gave the better prediction result, these is seen from load transfer that showed a good agreement with field results. The soil-structure interface modeling gave the great effect on the stress and displacement responses. The interface element modeling, which were developed could give the optimization on analyzes and design of geotechnical problems.